Women’s resilience and participation in climate governance in the agri-food sector: A strategic review of public policies - Mohammed, Kamaldeen; Najjar, Dina; Bryan, Elizabeth (International Center for Agricultural Research in the Dry Areas, 2022)
The primary objective of this working paper is to review literature (i.e., peer-reviewed and grey) on the extent to which women’s full and effective participation in climate change policies at different scales; defined at the level at which a policy is implemented, including macro, meso and micro; improve women’s resilience to climate change and environmental hazards. Given that women are vulnerable to climate change in unique ways and have important contributions to increase the climate resilience of the agri-food sector, it is imperative for governments to design and enact policies to enhance women’s resilience to climate change by alleviating gendered constraints and building women’s resilience capacities in line with the Sustainable Development Goals (SDG). The SDGs provide a goalpost for strengthening women’s voice and agency in climate resilience. In particular, SDG 5.5 which “seeks to ensure women’s full and effective participation and equal opportunities, defined as meaningful involvement and exertion of influence, for leadership at all levels of decision-making in political, economic and public life.” Improving women’s full, effective, and meaningful participation in the policy process is a critical pre-condition to increasing women’s resilience to climate change and disaster risk. As such, one of the central conclusions of the 65th Commission on the Status of Women (CSW65) reaffirmed the need for government policies to champion women’s full and effective participation and leadership in climate change governance. The review emphasizes government policies that promote women’s agency and voices in climate change resilience at multiple scales; national frameworks for integrating gender in climate policy, and women’s resilience capacities in the agri-food sector. Importantly, and when data allows, the review also details how and under what conditions these policies succeed in enabling women to acquire voice and agency in climate change resilience through specific well-being outcomes.